2016
DOI: 10.3402/iee.v6.30670
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of HCV in a Swedish county over 8 years (2002–2009) reveals distinct transmission patterns

Abstract: BackgroundHepatitis C virus (HCV) is a major public health concern and data on its molecular epidemiology in Sweden is scarce. We carried out an 8-year population-based study of newly diagnosed HCV cases in one of Sweden's centrally situated counties, Södermanland (D-county). The aim was to characterize the HCV strains circulating, analyze their genetic relatedness to detect networks, and in combination with demographic data learn more about transmission.MethodsMolecular analyses of serum samples from 91% (N=5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, in the current study, no association was observed between distinct HCV genotype and age, or HCV risk factors such as IVDA or blood transfusion. On the other hand, recent studies showed that HCV genotype 3a in IVD abusers and HCV genotype 1a in patients receiving blood or blood products were the most common genotypes (14,(49)(50)(51)(52). As shown in Table 2, genotype 3a was not the most frequent genotype just in IVDA donors.…”
Section: Discussionmentioning
confidence: 88%
“…However, in the current study, no association was observed between distinct HCV genotype and age, or HCV risk factors such as IVDA or blood transfusion. On the other hand, recent studies showed that HCV genotype 3a in IVD abusers and HCV genotype 1a in patients receiving blood or blood products were the most common genotypes (14,(49)(50)(51)(52). As shown in Table 2, genotype 3a was not the most frequent genotype just in IVDA donors.…”
Section: Discussionmentioning
confidence: 88%
“…Overall, genotypes 1 and 3 are the most frequent genotypes found in Swedish HCV-infected patients [21]. Among patients with transfusion-transmitted HCV infection, genotype 1a is most common, followed by genotype 2b [21][22][23], whereas genotype 3a is mainly associated with injecting drug use. Shev et al found a 21% prevalence of genotype 2b among Swedish blood donors in the early 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…Sentosa SQ HCV genotyping is a new automated deep sequencingbased assay that performs genotypes 1 to 6 determinations, 1a/1b subtype identification, and genotypes 4, 5 and 6 sub-typing. This compares favorably against Sanger sequencing of the NS5B region, the reference method for HCV genotype determination, except for HCV genotype 2 subtyping [2,97,98].…”
Section: Diagnosis Of Hcv Infection: General Considerationsmentioning
confidence: 99%